PENGARUH BUDAYA ORGANISASI DAN KARAKTERISTIK INDIVIDU TERHADAP EFEKTIVITAS ORGANISASI DI KANTOR KECAMATAN KOTA PADANG` - Onsardi, Onsardi; Nazilah, Ikhlatul Nazilah (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to determine the effect of organizational culture and individual Characteristics on organizational effectiveness in the subdistrict office of padang city.The population in this study was 32 people. The technique used is the data analysis used is t-test, f-test, multiple linier regression, and determinant coefficient test using SPSS 23. The results of calculations using SPSS show that there is an influence of organizational culture on organizational effectiveness, the influence of individual characteristics on organizational effectiveness, and the influence of organizational culture and individual characteristics on Organizational effectiveness. Keywords: organizational culture, individual characteristics, organizational efectiveness.